PKM Pendampingan dan Pelatihan Pemberdayaan Perempuan Melalui Aplikasi Pinterest - Damayanti Masduki; Yuliani Widianingsih; Hermina Simanihuruk (LPPM UNINUS, 2020)
One of the factors that made the group of mothers of the Islamic Association of Sukmajaya Wives in Depok not perfect in selling products, was the lack of knowledge about product diversity. Insight into product diversity can improve product quality, is still low and access to technology is still lacking. An introduction to knowledge of product diversity is needed to be developed to support the family's economy and support the group's independent business. The aim of the training activities is to provide understanding, knowledge and skills of the Persistri Women Group in Sukmajaya Depok District in conducting practices and activities in making handicraft accessories through the Pinterest application to further empower themselves so as to help improve entrepreneurial skills. The method of implementation in this community service program is through the introduction and assistance in the manufacture of handicraft accessories through the Pinterest application. From the results of the evaluation with the Chairperson of Persistri and the participants, training and mentoring on the introduction of Pinterest applications are very useful because in addition to knowing the various types of products. They can also look for various product references in accordance with their interests and even look for other products that can be used as examples and applied to the products they are interested in. Training activities are expected to not only be carried out with brooch accessory products, but also training of other products.